Analysis of The Influence of Digital Banking, Bopo and NPF on Profitability Levels of Sharia Commercial Bank - Mulatsih, Listiana Sri; Purnomo, Hadi; Prabantarikso, Mahelan; Dhamayanti, Sylvia Kartika; Sunarmi, Sunarmi (SENTRALISASI, 2024)
This study aims to analyze and examine the factors influencing of digital banking, operating costs to operating income (BOPO) and Non Performance Financing (NPF) on Return on Asset (ROA) in the Islamic Commercial Banks in period 2018-2022. The method of research is using the quantitative and regression analysis. The sample is Islamic Commercial Banks are consistenly publish financial report period 2018-2022 listed on the Indonesia Stock Exchange with a total sample of 3 companies. The sampling technique used a purposive sampling. The data analysed with IBM SPSS version 22 and was carried out by several tests such as validity test, realibility test, classic assumption test, linear regression analysis and coefficient of determination test. The results of this study indicate that the digital banking, BOPO and NPF simultaneously and significantly influence on ROA. The results of the partial test demonstrates that the digital banking and NPF has significant effect on ROA. While BOPO has a negative effect on ROA in the Islamic Commercial Banks in period 2018-2022. This research contributes to Islamic banking in order to make effective financing with results sharing and operational cost efficiency in operating income so that performance can be improve financial performance.